2004
DOI: 10.1002/sia.1700
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of liquid metal flow in the presence of an electric field: application to liquid metal ion source

Abstract: Two-dimensional axisymmetric flow of a viscous, incompressible liquid metal with a free boundary subject to the action of an electric field is investigated in the context of liquid metal ion source operation. It is established that an almost flat surface evolves with time into a cone-like shape, with the cone angle equal to Taylor's static value of 98.6• . The growth time of the Taylor cone and the time-dependent behaviour of basic physical quantities (electric field strength, fluid velocity and surface curvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…A goal of their study was to understand why electrohydynamic tip streaming resulting in the emission of a thin fluid jet from the conical tip does not occur in perfectly conducting or perfectly insulating liquids. Their simulations of perfectly conducting liquids also revealed tip sharpening with corresponding divergent behavior in the Maxwell, capillary and viscous normal stress at the apex, in agreement with previous studies [22,25,26] -however, they did not extract the corresponding values of the blow up exponents. Most interestingly, this study confirmed that tip-streaming requires the existence of interfacial tangential stresses near the conic tip, which are ultimately responsible for the cone-jet transition observed.…”
Section: More Recent Numerical Studies Of Conic Formation In Electrifsupporting
confidence: 83%
See 2 more Smart Citations
“…A goal of their study was to understand why electrohydynamic tip streaming resulting in the emission of a thin fluid jet from the conical tip does not occur in perfectly conducting or perfectly insulating liquids. Their simulations of perfectly conducting liquids also revealed tip sharpening with corresponding divergent behavior in the Maxwell, capillary and viscous normal stress at the apex, in agreement with previous studies [22,25,26] -however, they did not extract the corresponding values of the blow up exponents. Most interestingly, this study confirmed that tip-streaming requires the existence of interfacial tangential stresses near the conic tip, which are ultimately responsible for the cone-jet transition observed.…”
Section: More Recent Numerical Studies Of Conic Formation In Electrifsupporting
confidence: 83%
“…They also did not report the actual values obtained for the exponents characterizing the various divergent forces at the accelerating tip. Soon thereafter, there followed similar computational studies by Suvorov [25] and Suvorov and Zubarev [26] simulating the behavior of liquid gallium at the melting point at flow conditions corresponding to a smaller value of the Reynolds number. In these studies, the viscous normal stress term in the interface boundary condition was altogether omitted based on earlier indications [22] that the viscous term in the normal stress boundary condition tended to be much smaller than the capillary term.…”
Section: Numerical Studies By Suvorov Litvinov and Zubarevmentioning
confidence: 75%
See 1 more Smart Citation
“…There are publications showing the attraction and movement of liquid gallium metal toward a positive potential. 42 Other liquid metals, or even solid metals, can behave similarly; in fact, this is part of the basis of the field of electrohydrodynamics. Therefore, for LPE based electroepitaxy to occur, there is in fact no need to contact the liquid melt with physical electrodes, as was done by Novikov and Foxon.…”
Section: -9mentioning
confidence: 99%
“…A number of attempts have been made to understand the dynamics of LMIS. The formation of a Taylor cone was studied (Suvorov 2004;Suvorov and Zubarev 2004) by numerically solving the EHD equations for a free meniscus of viscous, incompressible and conducting fluid. The results show that pressures slowly increase until a critical time when they increase at a growing rate, that is, a singularity development.…”
Section: Dynamics Of Liquid Conesmentioning
confidence: 99%